2012
DOI: 10.1111/j.1463-1318.2012.03135.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and surgical treatment of rectal prolapse: an international survey

Abstract: The treatment of RP differs between surgeons, countries and regions. Guidelines are lacking. Prospective comparative studies are warranted that may result in universally accepted protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 18 publications
1
27
0
3
Order By: Relevance
“…Recently, laparoscopic ventral rectopexy (LVR) has gained wide acceptance [25] as the surgical treatment of rectal prolapse associated with low complication and recurrence rate [26]. The results of the current study might support LVR partly because the current study showed high incidence of young patients in Korea, relatively higher 5-year RFP in the AP group, and comparable complications.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, laparoscopic ventral rectopexy (LVR) has gained wide acceptance [25] as the surgical treatment of rectal prolapse associated with low complication and recurrence rate [26]. The results of the current study might support LVR partly because the current study showed high incidence of young patients in Korea, relatively higher 5-year RFP in the AP group, and comparable complications.…”
Section: Discussionmentioning
confidence: 62%
“…LVR is an established technique for the treatment of rectal prolapse and has been described for the treatment of rectoceles as well . As currently available studies tend to describe relatively small cohorts of patients, the aim of this study was to determine the influence of LVR on symptoms in a larger series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic ventral rectopexy (LVR) is the most popular technique in Europe for the treatment of external and internal rectal prolapse . Furthermore, it has been recommended for the treatment of large rectoceles .…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal operations through laparotomy or laparoscopy are frequently used for healthy, fit patients. The perineal approach is preferred in elderly, frail patients with many comorbidities or for strangulated and gangrenous rectal prolapse [5,7]. The most popular perineal procedures are Altemeier's perineal rectosigmoidectomy, which is preferred in the USA, and Rehn-Delorme's procedure, more commonly performed in Europe [8], the former being relatively complex and time-consuming to perform [9] and the latter having the drawback of a high recurrence rate [5].…”
Section: Introductionmentioning
confidence: 98%